Optimal loading for the development of peak power output in professional rugby players - Bevan, H. R.; Bunce, P. J.; Owen, N. J.; Bennett, M. A.; Cook, C. J.; Cunningham, D. J.; Newton, R. U.; Kilduff, L. P. (The Journal of Strength and Conditioning Research, 2010)
Optimal loading for the development of peak power output in professional rugby players. J Strength Cond Res 24(1): 43-47, 2010-The ability to develop high levels of muscular power is considered an essential component of success in many sporting activities; however, the optimal load for the development of peak power during training remains controversial. Our aim in the present study was to determine the optimal load required to observe peak power output during the ballistic bench throw (BBT) and squat jump (SJ) in professional rugby players. Forty-seven, professional, male, rugby players of (mean +/- SD) mass 101.3 +/- 12.8 kg and height 1.82 +/- 0.08 m volunteered and gave informed consent for this study, which was approved by a university ethics committee. Players performed BBT at loads of 20, 30, 40, 50, and 60% of their predetermined 1 repetition maximum (1RM) and SJ at loads of 0, (body mass only), 20, 30, 40, 50, and 60% of their predetermined 1RM in a randomized and balanced order. Power output (PO) was determined by measurement of barbell displacement with subsequent calculation of velocity, force, and power. Relative load had a significant effect on PO for both the BBT (effect size [eta]2: 0.297, p < 0.001) and SJ (Effect Size [eta]2: 0.709, p < 0.001). Peak power output was produced when the athletes worked against an external load equal to 30% 1RM for the upper body and 0% 1RM for the lower body.